Analisis Tindak Tutur Ilokusi Santri di Asrama Pondok Pesantren Tahfizul Qur’an Husnul Abror: An Illocutionary Speech Act Analysis of Students in the Dormitory of Tahfizul Qur’an Husnul Abror Islamic Boarding School - , Mislihatin (Lembaga Bale Literasi, 2025)
This study aims to describe the types of illocutionary speech acts used by students (santri) in their daily interactions at the dormitory of Pondok Pesantren Tahfizul Qur’an Husnul Abror. The research employs a pragmatic approach with a descriptive qualitative method. Data were collected through participant observation and documentation of natural utterances occurring in various contexts, such as mealtime, study sessions, worship activities, and peer interactions. The results indicate that the students utilize various types of illocutionary acts, particularly assertives, directives, and commissives. Assertive acts are used to convey information or opinions, directive acts to give commands or make requests, and commissive acts to express promises or commitments. The students' language choices reflect the unique linguistic environment of the pesantren, combining Indonesian, local languages (such as Sasak), and Arabic expressions. These findings reveal that student communication in the dormitory serves not only as a means of interaction but also as a reflection of their social, religious, and cultural values. This study is expected to contribute to the understanding of language practices in Islamic boarding schools and enrich the field of pragmatic studies in Indonesia.